PENGARUH KINERJA PEMBANTU KOLEKTOR TERHADAP PENCAPAIAN TARGET PAJAK BUMI DAN BANGUNAN DI KANTOR KECAMATAN DUA PITUE KABUPATEN SIDENRENG RAPPANG - Faturrahman Faturrahman; Muhammad Arisal Asad; Sapri Sapri (PRAJA: Jurnal Ilmiah Pemerintahan, 2021)
Effect of the performance of assistant collectors on the achievement of land and building tax targets at the Dua Pitue District Office, Sidenreng Rappang Regency. The population of this study was 95 people. The sampling technique used was saturated samples. This type of research is descriptive quantitative. Data collection techniques are observation, questionnaires, literature study. The data analysis technique used descriptive analysis, data quality test, classical assumption test. The results showed that the quality was 77%, the quantity was 72%. timeliness 60%, effectiveness 74%, independence 71%. The factors that affect the performance of the land and building tax target achievement 70% include personal 72%, 76% leadership, 72% team. 58% system, 73% contextual, measuring the performance of assistant collectors towards the achievement of land and building tax targets at the Dua Pitue District Office, Sidenreng Rapappang district is 71% of the 100% expected results, which is categorized as "good".